Carbon dioxide electroreduction over imidazolate ligands coordinated with Zn(II) center in ZIFs. (October 2018) - Jiang, Xiaole; Li, Haobo; Xiao, Jianping; Gao, Dunfeng; Si, Rui; Yang, Fan; Li, Yanshuo; Wang, Guoxiong; Bao, Xinhe
Abstract: Metal-organic frameworks (MOFs), combining the favorable characteristics of heterogeneous and homogeneous catalysts, have been explored as a novel class of model catalytic materials for understanding electrochemical CO2 reduction reaction (CO2 RR). MOFs exhibit high Faradaic efficiency of CO2 RR, but suffer from limited current density of CO2 RR (typically lower than 3.4 mA cm −2 ). Herein, we investigate zeolitic imidazolate frameworks (ZIFs) including ZIF-8, ZIF-108, ZIF-7 and SIM-1 with the same SOD (sodalite) topology and different organic ligands for CO2 RR in aqueous electrolyte. ZIF-8 shows the highest CO Faradaic efficiency of 81.0% at − 1.1 V (vs. reversible hydrogen electrode, RHE) among the four ZIF catalysts, and the highest CO current density can reach 12.8 mA cm −2 at − 1.3 V (vs. RHE) over ZIF-108. In situ X-ray absorption spectroscopy measurements and density functional theory calculations indicate that the imidazolate ligands coordinated with the Zn(II) center in ZIFs are the active sites for CO2 RR, determining the CO Faradaic efficiency and current density over ZIFs. Graphical abstract: Imidazolate ligands coordinated with the Zn(II) center in zeolitic imidazolate frameworks are proposed to be the active sites for catalyzing electrochemical CO2 reduction reaction in aqueous electrolyte. fx1 Highlights: Zeolitic imidazolate frameworks catalyze electrochemical CO2 reduction reaction. ZIF-8 shows the maximum CO Faradaic efficiency among the four catalysts. The ligands coordinated with Zn(II) center are proposed to be the active sites.